The Improvement of Students' Arabic Speaking Skills: The Role of Interactive Strategies and the Establishment of a Language Environment - Muhammad Fadhlan; imam Asrori; Sutaman; Alif Cahya Setiyadi (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2024)
The goals of this research were to learn about the many tactics used by teachers to develop Arabic speaking skills in Pondok Modern Darussalam Gontor, and explain the various Arabic environments that help students improve their Arabic speaking skills at Pondok Modern Darussalam Gontor. This is a qualitative study conducted using a case study approach. The process of gathering information through observation, interviews, and documentation. Data Analysis Techniques comprise four steps: 1) collecting data, 2) integrating data, 3) condensing data distribution, and 4) drawing conclusions from data. The findings of this study indicate that: (1) Pondok Modern Darussalam Gontor's technique for increasing Arabic speaking skills is divided into classroom and out-of-classroom learning. Classroom learning methods include direct strategy, dialogue strategy, discussion strategy, and question and answer strategy. Outside of the classroom, there are two types of language justification strategies: direct and shared. (2) The Arabic Language Environment, which includes the development of students' confidence in speaking Arabic, as well as Discussion activities such as Vocabulary Division and Repetition, Arabic Speech, and Punishment for Violating the Official Language, contribute significantly to students' Arabic speaking skills. 3) Develop several techniques to increase pupils' speaking skills in Modern Darussalam gontor.